The influence of menopause on urinary incontinence in the women of the community: a cross-sectional study from North India - Khan, Samreen; Ansari, M. Athar; Vasenwala, Shaista M.; Mohsin, Zehra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Urinary incontinence is defined as the complaint of any involuntary loss of urine that is a social or hygienic problem. Worldwide, over 200 million people are living with urinary incontinence and as the life expectancy of women is increasing, more number of women are bound to suffer from it. The aim of the present study is to find out the effect of menopause on the occurrence of Urinary Incontinence in women and to find out risk factors in post-menopausal women associated with Urinary Incontinence. Methods: It was a community based cross-sectional study involving post-menopausal women living in the urban and rural areas registered under Community Medicine, J.N. Medical College, Aligarh, India. A total of 530 women were taken for this study. Descriptive statistics as well as simple proportion were calculated with SPSS 20.0. Tests of significance and Binary Logistic regression analysis were used for analysis. Results: Significant differences were found in the association of Urinary Incontinence with increasing age groups and consequent years spent in menopause, rural area of residence, illiteracy, lower socio-economic class, inadequate housing standards, obesity, smoking, parity, history of hysterectomy, and co-morbidities such as Urinary Tract Infection and Pelvic organ prolapse. Conclusions: From a public health perspective, there is considerable opportunity to improve women’s quality of life by increasing health education about urinary incontinence and its treatment by taking steps for life style modifications.